1996
DOI: 10.1002/mds.870110308
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil function, nitric oxide, and blood oxidative stress in Parkinson's disease

Abstract: We studied nitrogen radical nitric oxide (.NO) release and reactive oxygen species (ROS) production by isolated neutrophils after phorbol myristate acetate (PMA) stimulation in 12 newly diagnosed and nine treated Parkinson's disease (PD) patients and 10 age-matched healthy controls. Neutrophils of both groups of PD patients had an elevated PMA-activated release of .NO [61 and 57%, respectively, higher than that of controls (p < 0.05)]. In contrast, H2O2 release was only significantly increased by 56% in chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 32 publications
(18 reference statements)
2
24
0
Order By: Relevance
“…Nitrite content was increased in PD patients that carry any genotype of nNOS exon 29 or heterozygous variant genotype of exon 18 as compared with respective controls. This is in accordance with the previous studies that have shown an increased nitrite content and nNOS activity in the PMNs of PD patients [28,29]. Such observations suggest that nNOS exon 29 polymorphism and heterozygous variant of exon 18 could be associated with PD risk.…”
Section: Discussionsupporting
confidence: 94%
“…Nitrite content was increased in PD patients that carry any genotype of nNOS exon 29 or heterozygous variant genotype of exon 18 as compared with respective controls. This is in accordance with the previous studies that have shown an increased nitrite content and nNOS activity in the PMNs of PD patients [28,29]. Such observations suggest that nNOS exon 29 polymorphism and heterozygous variant of exon 18 could be associated with PD risk.…”
Section: Discussionsupporting
confidence: 94%
“…Oxidative stress is the basic precursor for almost all the deadly diseases and PD is also one among them [3]. Thus, it has been focused to find natural antioxidants such as curcumin, epigallocatechin-3-gallate, melatonin and so on to treat PD [4].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic alterations in circulating blood cells are widely accepted as representative of similar central nervous system changes in human PD. Increased NO release of neutrophils and decreased catalase activity in erythrocytes were observed at the beginning of PD; H 2 O 2 release by neutrophils and mitochondrial impaired function may be later signs in PD (Gatto et al, 1996).…”
Section: Inflammationmentioning
confidence: 94%
“…Oxidative stress promotes aggregation and accumulation of -synuclein, characteristic of Parkinson's disease (Kozlowski et al, 2009;Opazo et al, 2003). The series of observed changes include glycation protein oxidation, lipid peroxidation, depletion of antioxidants and nucleic acid oxidation (Famulari et al, 1996;Gatto et al, 1996;Gatto et al, 1997;Repetto et al, 1999;Fiszman et al, 2003;Repetto, 2008). It has been proposed that oxidative damage favors the aggregation of -synuclein in sporadic PD.…”
Section: Oxidative Stress and Oxidative Damagementioning
confidence: 99%
See 1 more Smart Citation